Health risk assessment of exposure to heavy metals via consumption of three tadpole species found in surrounding electronic waste dumpsite in Kalasin province - Intamat, Somsak; Ya-ngam, Dawprakay; Raksapakdee, Varitsara; Neeratanaphan, Lamyai (Disease Control Journal, 2022)
This research was conducted to assess health risks from exposure to heavy metals (arsenic, cadmium, chromium, lead, nickel, copper, and manganese) via consumption of three tadpole species (Kaloula pulchra, Fejervarya limnocharis, and Hoplobatrachus rugulosus) found in the surrounding areas of an electronic waste dumpsite in Khong Chai district, Kalasin province. Heavy metals contamination in water, sediment, and three tadpole species were assessed. The samples were analyzed for heavy metals using inductively coupled plasma optical emission spectrometry (ICP-OES). Health risk assessments through three tadpole species consumption was conducted based on hazard quotient (HQ). The results found that all heavy metal concentration in water samples exceeded the standards for water sources, whereas arsenic concentration in sediment samples was found to have exceeded the standards for soil used for the purposes other than agricultural and residential purposes. Regarding heavy metal contamination in three tadpole species, it was found that arsenic, chromium, and lead concentration exceeded the standard contamination in foods (at 0.1, 1.0 and 0.3 mg/kg, respectively), whereas cadmium concentration (0.5 mg/kg) exceeded the standard level only in Fejervarya limnocharis. Health risk assessment of exposure to heavy metals through the consumption of three tadpole species found that the HQ values of lead in three tadpole species were more than 1, whereas the HQ of arsenic was more than 1 only in Fejervarya limnocharis tadpole. E-waste disposal that was not appropriately managed has led to contamination of toxic substances into the environments and detrimental impacts to human health and ecosystem both in the short and long term.